The vibration and coefficient of restitution analysis in tennis rackets varied with material composition and fiber arrangement - Chen, T.-Y.; Chiang, J.-Y.; Chiang, C.-C.; Yang, J.-H.; Lin, D. C. (ISB Congress, 2005)
This study was to investigate how the vibration on wrist joint of the player and rebounding velocity of the ball from each racket were affected by the vibration of various tennis rackets which were composed by the mixture of carbon fiber and glass fiber. Because of the results it was concluded: By increasing the content of glass fiber in the racket, it might off-center impact. But it would affect the performance on ball rebound. On the other hand, the rackets with fiber angle at 22 degrees had lower vibration than that at 30 degrees.